Effective dose to patient measurements in flat-detector and multislice computed tomography: a comparison of applications in neuroradiology - Struffert, Tobias; Hauer, Michael; Banckwitz, Rosemarie; Koehler, Christoph; Royalty, Kevin; Dörfler, Arnd (European Radiology, 2014)
Flat-detector CT (FD-CT) is used for a variety of applications. Additionally, 3D rotational angiography (3D DSA) is used to supplement digital subtraction angiography (DSA) studies. The aim was to measure and compare the dose of (1) standard DSA and 3D DSA and (2) analogous FD-CT and multislice CT (MSCT) protocols.Using an anthropomorphic phantom, the effective dose to patients (according to ICRP 103) was measured on an MSCT and a flat-detector angiographic system using standard protocols as recommended by the manufacturer.(1) Evaluation of DSA and 3D DSA angiography protocols: ap.-lat. Standard/low-dose series 1/0.8 mSv, enlarged oblique projection 0.3 mSv, 3D DSA 0.9 mSv (limited coverage length 0.3 mSv). (2) Comparison of FD-CT and MSCT: brain parenchyma imaging 2.9 /1.4 mSv, perfusion imaging 2.3/4.2 mSv, temporal bone 0.2 /0.2 mSv, angiography 2.9/3.3 mSv, limited to the head using collimation 0.5/0.5 mSv.The effective dose for an FD-CT application depends on the application used. Using collimation for FD-CT applications, the dose may be reduced considerably. Due to the low dose of 3D DSA, we recommend using this technique to reduce the number of DSA series needed to identify working projections.Effective dose of FD-CT in comparison to MSCT is in comparable range. Collimation decreases the dose of FD-CT effectively. Effective dose of 3-D angiography is identical to 2-D DSA. Different FD-CT programs have different dose.
EVALuna2:22994